KONSEP BANTUAN HUKUM KONSTITUSIONAL : Kodrat Manusia Mendapatkan Access to Justice - Krisnapati, S.H., M.H., Bayu (Justitia et Pax, 2018)
The realization of social justice for all population, especially for poor and disadvantaged people as implementation access to justice completely, so there is no legal term only for able and rich people, but legal for all. This research focuses on constitutional legal aid concept and wishes to be implemented in Indonesia. This study uses normative juridical approach, the analysis use qualitative descriptive with secondary data sources. Conclusions obtained, the concept of constitutional legal aid is feasible and must be applied in Indonesia on the basis of constitutions order, by changing the law on legal aid through judicial review.